The Relationship Between Caregiving and Mortality After Accounting for Time-Varying Caregiver Status and Addressing the Healthy Caregiver Hypothesis - Fredman, Lisa (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND. Previous studies have shown inconsistent associations between caregiving and mortality. This may be due to analyzing caregiver status at baseline only, and that better health is probably related to taking on caregiving responsibilities and continuing in that role. The latter is termed The Healthy Caregiver Hypothesis, similar to the Healthy Worker Effect in occupational epidemiology. We applied common approaches from occupational epidemiology to evaluate the association between caregiving and mortality, including treating caregiving as time-varying and lagging exposure up to 5 years. METHODS. Caregiving status among 1,068 women (baseline mean age = 81.0 years; 35% caregivers) participating in the Caregiver-Study of Osteoporotic Fractures study was assessed at five interviews conducted between 1999 and 2009. Mortality was determined through January 2012. Cox proportional hazards models were used to estimate adjusted hazard ratios and 95% confidence intervals adjusted for sociodemographics, perceived stress, and functional limitations. RESULTS. A total of 483 participants died during follow-up (38.8% and 48.7% of baseline caregivers and noncaregivers, respectively). Using baseline caregiving status, the association with mortality was 0.77, 0.62–0.95. Models of time-varying caregiving status showed a more pronounced reduction in mortality in current caregivers (hazard ratios = 0.54, 0.38–0.75), which diminished with longer lag periods (3-year lag hazard ratio = 0.68, 0.52–0.88, 5-year lag hazard ratios = 0.76, 0.60–0.95). CONCLUSIONS. Overall, caregivers had lower mortality rates than noncaregivers in all analyses. These associations were sensitive to the lagged period, indicating that the timing of leaving caregiving does influence this relationship and should be considered in future investigations.